A;15:(x+2)=3
x+2=15:3
x+2=5
x=5-2
x=3
Vậy x=3
a ) \(15:\left(x+2\right)=3\)
\(\left(x+2\right)=15:3\)
\(x+2=5\)
\(x=5-2\)
\(x=3\)
Vậy \(x=3\)
b) \(20:\left(1+x\right)=2\)
\(\left(1+x\right)=20:2\)
\(1+x=10\)
\(x=10-1\)
\(x=9\)
Vậy \(x=9\)
c) \(240:\left(x-5\right)=2^2.5^2=20\)
\(240:\left(x-5\right)=4.25=20\)
\(240:\left(x-5\right)=100=20\)
\(\Rightarrow\orbr{\begin{cases}240:\left(x-5\right)=100\\240:\left(x-5\right)=20\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}\left(x-5\right)=240:100\\\left(x-5\right)=240:20\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x-5=2,4\\x-5=12\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=2,4+5\\x=12+5\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=7,4\\x=17\end{cases}}\)
Vậy \(x=7,4\)hoặc \(x=17\)
d) \(96-3\left(x+1\right)=12\)
\(3\left(x+1\right)=96-12\)
\(3\left(x+1\right)=84\)
\(\left(x+1\right)=84:3\)
\(x+1=28\)
\(x=28-1\)
\(x=27\)
Vậy \(x=27\)
Chúc bạn học tốt !!!
a)15:(x+2)=3
=>x+2 =15:3
=>x+2 =5
=>x =5-2
=>x =3
b)20:(1+x)=2
=>1+x =20:2
=>1+x =10
=>x =10-1
=>x =9
c)240:(x-5)=22.52=20
Đề câu c sai òi.
d)96-3(x+1)=12
3(x+1)=96-12
3(x+1)=84
x+1 =84:3
x+1 =28
x =28-1
x =27
a) 15:(x+2)=3
x+2=15:3
x+2=5
x=5-2
x=3
vậy x=3
b) 20:(1+x)=2
1+x=20:2
1+x=10
x=10-1
x=9
vậy x=9
c) 240:(x-5)=22.52=20
240:(x-5)=20
x:5=240:20
x:5=12
x=12.5
x=60
vậy x=60
d) 96-3(x+1)=12
3(x+1)=96-
sorry làm lại câu d
d) 96-3(x+1)=12
3(x+1)=96-12
3(x+1)=84
x+1=84:3
x+1=28
x=28-1
x=27
vậy x=27